Stunting Pada Anak Usia Dini - Erik Erik (IAI Bunga Bangsa Cirebon, 2020)
Malnutrition and stunting are two interrelated problems. Stunting in children is the result of nutrient deficiency during the first thousand days of life. This causes irreversible disturbances in the physical development of the child, causing a decrease in work performance. Stunted children had a mean Intelligence Quotient (IQ) score, eleven points lower than the average IQ score in normal children. Disorders of growth and development in children due to malnutrition if they do not get intervention from an early age will continue into adulthood. The research method used is a phenomenological qualitative method. Researchers will examine cases of stunting in Mirat Village, Lewimunding District, Majalengka Regency. Sample 2 children who were stunted in Mirat Village, Lewimundin District. Research data source UPTD Puskesmas Lewimunding District. Based on the results of researchers' interviews with nutritionists and environmental health workers (Kesling), as well as observations of two stunted children as well as interviews with parents, it was found that the factors that influence stunting are as follows: a diet that does not fulfill a balanced nutrition during the pregnancy process. and after the baby is born, the child's diet from birth to two years of age, exclusive breastfeeding for less than 6 months, complementary feeding (complementary feeding) too early (less than six months), improper parenting (often yelling at children, less close to children, taking actions that make children away from their parents), poor environmental sanitation, not introducing toilet training to children early on, and genetics does not have a significant role in the incidence of stunting Abstrak Kurang gizi dan stunting merupakan dua masalah yang saling berhubungan. Stunting pada anak merupakan dampak dari defisiensi nutrient selama seribu hari pertama kehidupan. Hal ini menimbulkan gangguan perkembangan fisik anak yang irreversible, sehingga menyebabkan penurunan performa kerja. Anak stunting memiliki rerata skor Intelligence Quotient (IQ) sebelas poin lebih rendah dibandingkan rerata skor IQ pada anak normal. Gangguan tumbuh kembang pada anak akibat kekurangan gizi bila tidak mendapatkan intervensi sejak dini akan berlanjut hingga dewasa. Metode penelitian yang digunakan ialah metode kualitatif fenomenologi. Peneliti akan meneliti kasus stunting di Desa Mirat Kecamatan Lewimunding Kabupaten Majalengka. Sampel 2 anak yang mengalami stunting di Desa Mirat Kecamatan Lewimundin. Sumber data Penelitian UPTD Puskesmas Kecamatan Lewimunding. Berdasarkan hasil wawancara peneliti dengan ahli gizi dan petugas kesehatan lingkungan (kesling), serta dilakukan pula observasi kepada dua anak stunting juga wawancara kepada orangtua, ditemukan bahwa faktor-faktor yang memengaruhi stunting ialah sebagai berikut: pola makan yang tidak memenuhi gizi seimbang selama proses kehamilan dan setelah bayi lahir, pola makan anak sejak lahir sampai usia dua tahun, pemberian ASI eksklusif yang kurang dari 6 bulan, pemberian Makanan Pendamping ASI (MPASI) terlalu dini (kurang dari enam bulan), pengasuhan orangtua yang kurang tepat (sering membentak anak, kurang dekat dengan anak, melakukan tindakan yang membuat anak menjauh dari orangtua), sanitasi lingkungan yang kurang baik, tidak mengenalkan toilet training kepada anak sejak dini, dan genetic tidak memiliki peran signifikan terhadap kejadian stunting